Profile Of Clinically Suspected Encephalitis Patients Admitted To Faridpur Medical College Hospital, Bangladesh - Fattah, SA; Sarker, SK; Ali, MY; Alam, MT; Ali, SY (Faridpur Medical College Journal, 2011)
Encephalitis is a relatively common clinical diagnosis of admitted patients in Faridpur Medical College Hospital. This is significant because there was an outbreak of Nipah Virus (Ni-V) encephalitis in Faridpur district in 2004 with 34 cases including 26 deaths. Recent death of an intern doctor of FMCH from Ni-V encephalitis further emphasizes the gravity of situation. In this study a total number of 100 cases of clinically suspected encephalitis patients were studied for different clinical parameters. This is a retrospective study using data from hospital records. Majority of patients presented with neurological features (85%), 6% with pulmonary, 7% with combined neurological and pulmonary, and 2% with other features. 5-18 years age group comprises the highest number 44%, followed by >18 years age group 34%. Male-female ratio was 33:17. July to November was the period of maximum number of admission, the highest being in August. Patient from all upazillas of Faridpur were admitted, the highest being from Sadar Upazilla. 48% of the patients recovered, 19% expired and 7% were referred. In this context, further prospective study is urgently required to find out the epidemiological characteristics of Nipah virus encephalitis in Faridpur region. DOI: 10.3329/fmcj.v5i2.6818 Faridpur Med. Coll. J. 2010;5(2):38-40